Upaya Peningkatan Kualitas Produk UMKM Makanan Minuman di Surabaya Melalui Pelatihan Keamanan Aditif dan Kemasan Pangan serta Program Self Declare Halal Menggunakan Aplikasi SEHATI: Efforts to Improve the Quality of Food and Beverage MSME Products in Surabaya Through Additive and Food Packaging Safety Training as well as a Self-declare Halal Program Using the SEHATI Application - Nofianti, Kholis Amalia; Ekowati, Juni; Purwanto, Bambang Tri; Prayoga , Adistiar; Yuwono, Mochammad; Prayoga, Adistiar; Rijal, Muhammad Agus Syamsur; Suciati, Suciati; Paramita, Diajeng Putri; Sulistyowaty, Melanny Ika; Hakim, Luqmanul (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
MSMEs in the food sector are the dominant economic support in Indonesia. Surabaya has more than 60 thousand MSMEs. In food production at the MSME level, food additives and packaging is inevitable. Despite the current regulations, people still encounter dangerous food additives or packaging. This is caused by a lack of knowledge and awareness of food producers and consumers. On the other hand, since the implementation of the halal guarantee system, the use of halal labels on food and beverage products has become very important. For MSMEs, the government makes it easy to get a halal label through the self-declare halal program using the SEHATI. This activity aims to provide training on safe food additives and packaging, halal food, and the self-declare halal program using the SEHATI application in Surabaya. Carrying out activities using presentation and two-way interaction. Evaluate activities through pretest and posttest for each topic. The lowest values for food packaging, it is 52.92 and 79.58. The highest value was shown by the halal topic with an average of 69.58 and 97.92. The significance of the increase in value was demonstrated by the Wilcoxon test using SPSS 22 which showed the Asymp. Sig (2-tailed) value for the three topics less than 0.05. Thus, it can be concluded that this activity has proven to be able to improve participants' abilities regarding safe food additives and packaging, as well as halal food and the introduction of the self-declare halal program.